The Effect of the Johari Window Self-Awareness Training on Teenagers’ Self-Confidence at Aisyiyah Orphanage in Sidoarjo - Ajeng Destya Ramadhani Warsito; Widyastuti Widyastuti (Program Studi bimbingan Konseling PPs UNM Makassar, 2022)
This research is aimed to increase the self-confidence of teenagers living at Aisyiyah Orphanage in Sidoarjo by using the Johari Window self-awareness training. This study implemented a quasi-experimental treatment group with pre-treatment and post-treatment assessments. To test the effectiveness, this study used Paired Sample T-Test and the results showed that there was a difference in self-confidence scale between pre-test and post-test results. The hypothesis in this study was there are differences in the level of self-confidence among teenagers before and after the Johari Window self-awareness training. To test the hypothesis, an analysis of paired T-Test data using the JASP application was carried out. Based on the results of the analysis, teenagers generally experienced an increase in self-confidence by 2,200 (SE: 0,530) after the Johari Window self-awareness training. The paired sample t-test showed a significant increase in self-confidence (t (30) = -4.147, p < .001) and the Cohen's d value showed an effect of 0.757. Based on these results, the hypothesis in this study was accepted since it illustrates that experimental training using the Johari Window training method can increase self-confidence of the teenagers at Aisyiyah Orphanage in Sidoarjo.